2022
DOI: 10.3389/fnagi.2022.881239
|View full text |Cite
|
Sign up to set email alerts
|

A Review of ApoE4 Interference Targeting Mitophagy Molecular Pathways for Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is one of the major worldwide causes of dementia that is characterized by irreversible decline in learning, memory loss, and behavioral impairments. Mitophagy is selective autophagy through the clearance of aberrant mitochondria, specifically for degradation to maintain energy generation and neuronal and synaptic function in the brain. Accumulating evidence shows that defective mitophagy is believed to be as one of the early and prominent features in AD pathogenesis and has drawn atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 175 publications
1
7
0
Order By: Relevance
“…An inability to meet energetic demand due to mitochondrial damage can trigger mitochondrial fusion to compensate for diminished mitochondrial output. Accordingly, apoE3 astrocytes exposed to aggregated tau demonstrated an increase in the levels the mitochondrial fusion protein MFN1, consistent with prior reports of tau-induced MFN1 accumulation and mitochondrial dysfunction (Chen et al, 2022;Kandimalla et al, 2016;Li et al, 2016). Despite this initial compensatory response, our transcriptomic results and prior reports indicate that prolonged tau accumulation in astrocytes may contribute to functional impairments (Reid et al, 2020) that are detrimental to surrounding neurons, via altered calcium signaling (Piacentini et al, 2017), impaired glutamate regulation (Dabir et al, 2006;Li Puma et al, 2022) and cellular senescence (Ungerleider et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…An inability to meet energetic demand due to mitochondrial damage can trigger mitochondrial fusion to compensate for diminished mitochondrial output. Accordingly, apoE3 astrocytes exposed to aggregated tau demonstrated an increase in the levels the mitochondrial fusion protein MFN1, consistent with prior reports of tau-induced MFN1 accumulation and mitochondrial dysfunction (Chen et al, 2022;Kandimalla et al, 2016;Li et al, 2016). Despite this initial compensatory response, our transcriptomic results and prior reports indicate that prolonged tau accumulation in astrocytes may contribute to functional impairments (Reid et al, 2020) that are detrimental to surrounding neurons, via altered calcium signaling (Piacentini et al, 2017), impaired glutamate regulation (Dabir et al, 2006;Li Puma et al, 2022) and cellular senescence (Ungerleider et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The mechanism underlying this impairment is likely multifactorial, though prior groups have suggested that the apoE4‐induced Ca 2+ dysregulation in astrocytes (Larramona‐Arcas et al, 2020) can disrupt mitochondrial fusion complex formation (Ishihara et al, 2017). Interestingly, studies have demonstrated that apoE4 expression in astrocytes can significantly alter mitochondrial physiology through multiple mechanisms including dysregulated mitochondrial dynamics, maintenance, and fuel flexibility (Chen et al, 2022; Qi et al, 2021; Schmukler et al, 2020). The current findings suggest that the diminished energetic output by astrocytes in the presence of pathogenic proteins like tau, coupled with the inability of apoE4 astrocytes to initiate a compensatory mitochondrial response, ultimately reduces neuronal support, thereby increasing the regional neuronal susceptibility to chronic neurodegenerative insults.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, ApoE4 elicited mitochondrial dysfunction, further rendering it vulnerable to stimuli, such as LPS, which could be followed by mitophagy deficits, exacerbated neuroinflammation and depression. Furthermore, ApoE4 carriers and transgenic mice demonstrated mitochondrial structural and functional abnormalities, including elevated oxidative and mitochondrial dysfunction, possibly through ApoE4 proteolytic fragments that selectively target mitochondria and impair mitochondrial functions, such as dynamic disturbance, deficits in mitochondrial membrane integrity, defects in electrochemical potential and reduced mitochondrial respiratory activity 60–65 . Previous studies have shown that ApoE4 is associated with impaired astrocyte autophagy and the dysregulation of genes involved in mitochondrial dynamics 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient mitochondrial quality control may underlie the decreased mitochondrial respiration also observed in the cortex of aged ApoE4 but not ApoE3 mice 75 . However, as some of these changes may also occur via transcriptional regulation 76 , the proportion of PINK1 attenuation via AMPK-mediated sequestering of Pink1 mRNA on mitochondria in vivo needs to be determined experimentally.…”
Section: Discussionmentioning
confidence: 99%